EDUKASI PEDULI SAMPAH PADA SISWA SEKOLAH DASAR MADRASAH IBTIDA’IYAH NURUL HUDA KABUPATEN FAKFAK - Nelson Rumui; Syukron Anas; Deisya Al Hamid (P3M Politeknik Negeri Malang, 2025)
Awareness of the importance of protecting the environment should not only be owned by everyone, both adults and children. Environmental education in elementary school is crucial because it is at this stage that children begin to understand the values of life and the importance of their role in keeping the environment clean. Currently, SD MI Nurul Huda Pasir Putih is committed to raising environmental awareness among students as part of character education. Based on the team's observation, the school does not yet have a structured special education program on waste management and environmental awareness. Most environmental learning activities are still general in nature and do not focus on concrete actions that can be applied by students in their daily lives. In addition, the school also faces limitations in terms of resources and learning materials that support environmental education programs. This activity was initiated to provide students with a deeper knowledge and understanding of the importance of keeping the environment clean, as well as teaching them how to manage waste properly. It is hoped that students can apply this knowledge in their daily lives and become agents of change in their neighborhood. The stages of this activity are preparation and survey, material delivery and interactive activities, documentation, evaluation, feedback collection, reporting, and follow-up. The team hopes that similar activities can be carried out in other schools, even from an early childhood education level.